DESOSPITALIZAÇÃO PSIQUIÁTRICA E PROMOÇÃO DA SAÚDE EM RESIDÊNCIA TERAPÊUTICA - PORTO, FLÁVIA FIGUEIRA DE ANDRADE (2017)
The de-hospitalization of people with a long-term history in psychiatric hospitals is a priority among public mental health policies in Brazil, which consider the rupture of family and social life aggravating the process of psychic illness. In order to provide care for these people outside the hospitals, health facilities were created, such as therapeutic residences, community-based housing with the assistance of daily caregivers. This work was the result of the professional experience of the psychologist accompanying the dehospitalization of thirty patients to three new therapeutic residences in the city of São José dos Campos / SP. Based on Winnicott's psychoanalysis, this research described and analyzed the experience of de-hospitalization and health promotion in this context, with emphasis on the group interactions and experiences of the residents in the hospital and residential space, in care and community relations. The instruments used were: participant observation and interview based on a previously elaborated script with the residents. The results indicated that the interactions and experiences in the therapeutic residency, for the most part, were kept rigid by rules and restrictions in the occupation of the home space, handling of personal belongings and circulation in the community; The care relationships demanded an active presence of the care agents, especially in the attention to the body, in the management of psychopathological symptoms and in the mediation of conflicts with the neighborhood and other people in the community. It was concluded that care relationships, even in de-hospitalization circumstances, can trap subjects and inhibit creative processes, as well as repercussions in the prevention of acute psychotic crisis and rehospitalization. The challenge in promoting health in therapeutic residency was to overcome situations that make it impossible for the residents to be in life with all their excesses, particularities and needs of attention and adapted care.